Effectiveness of Organizational Design through Implementation of Regional Development Policy - Laurens, Samson; Yusriadi, Yusriadi; Zulkifli, Zulkifli (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2020)
This study aims to analyze the implementation of Regional Arrangement Policy according to Regional Regulation No. 4 of 2016 in Realizing the Effectiveness of Organizational Design of South Buru Regency based on four indicators: 1) excellent communication demonstrated by friendly employee behavior, polite to the people who need services, but still constrained by the low awareness of the community to follow and obey the required provisions, 2) employee resources are sufficient in terms of quantity, but even need to improve discipline in terms of time and suitability and consistency with the requirements set out in completing service tasks to ensure accountability employee performance, 3) disposition has been implemented well as indicated by the high awareness of all elements of the leadership and employees of the duties, responsibilities and authority as a public servant and 4) bureaucratic structures running In accordance with the main tasks and functions, indicated by the application of the rules relating to the provisions of service activities in accordance with work procedures in each field.